Validación de instrumento que mide la educación disruptiva en la formación clínica. - Omar Saenz-Acuña, Angel; Parra-Acosta, Haydeé (Revista Medica del IMSS)
Background: During the contingency derived from the COVID-19 pandemic, there were no instruments assessing the aspects of clinical training, which is why it is necessary to have a questionnaire that let us know the opinion of medical students about the disruptive education. Objective: To validate a questionnaire designed to know the opinion of medical students about disruptive education in their clinical training. Material and methods: This is a validation cross-sectional study which was developed in three phases: 1) Elaboration of the questionnaire aimed at undergraduate medical students who took clinical science subjects in their curricular program; 2) validation of content by Aiken's V test with 7 expert judges and reliability estimation with Cronbach's alpha coefficient in a pre-sample test with 48 students; 3) analysis of the information through descriptive statistics, where the following results were observed: Aiken's V index of V = 0.816; Cronbach's alpha coefficient = 0.966. A total of 54 items were incorporated in the questionnaire after the pre-sampling test. Conclusions: We can rely on a valid and reliable instrument that objectively measures disruptive education in the clinical training of medical students.